Penerapan Model Station Rotation untuk Meningkatkan Penguasaan Konsep dan Keterampilan pada Mata Pelajaran Bahasa Inggris - Mikawati Mikawati; Nancy Susianna (Jurnal Syntax Admiration, 2024)
This study aims to evaluate the effectiveness of the Station Rotation learning model in improving students' mastery of concepts and skills in United Kingdom subjects in grade III. The research was conducted in three cycles, each with an approach that involved the use of different stations for learning, exercise, and evaluation. The results show that the application of this model significantly improves students' ability to understand the material and communication skills. The increase in the average competency score of students in designing learning, communicating, and using the United Kingdom was recorded from cycle one to cycle three. However, challenges still exist in terms of material understanding and use of technology, which indicates the need for further adjustments in learning methods and the provision of adequate facilities. Overall, the Station Rotation model has proven to be effective in improving students' collaboration skills and understanding of United Kingdom concepts.